أثر تبني التسويق الداخلي على جودة الخدمة الصحية ( دراسة حالة المؤسسة الاستشفائية العمومية ابراهيم تريشين البليدة) - تبوب, عبد العالي (جامعة الوادي - University of Eloued, 2023)
This study aims to test the effect of adopting internal marketing on the quality of health service in Algerian health institutions, the impact of the internal marketing elements of employee selection, training, motivation, empowerment and internal communications on health service quality was tested, the study sample consisted of 100 employees of the Ibrahim Trichin Public Hospital Corporation in Blida, The questionnaire was used as a tool for data collection and included three parts, The data was analyzed using the SPSS statistical program, The study concluded that internal marketing with its combined dimensions does not have a positive impact on the quality of the health service provided in the institution.
The impact of adopting internal marketing on health service quality (a case )study of the public hospital institution Ibrahim Trichin in Blida
مقال
Keywords: تسويق داخلي؛ جودة خدمة صحية؛ رضا العاملين; Internal marketing; Health service quality; Employee satisfaction